Examining Health Outcomes in Juvenile Idiopathic Arthritis: A Genetic Epidemiology Study. Issue 4 (25th January 2022) - Clarke, Sarah L. N.; Richmond, Rebecca C.; Zheng, Jie; Spiller, Wes; Ramanan, Athimalaipet V.; Sharp, Gemma C.; Relton, Caroline L.
Abstract : Objective: Juvenile idiopathic arthritis (JIA) is the most common pediatric rheumatic disease; however, little is known about its wider health impacts. This study explores health outcomes associated with JIA genetic liability. Methods: We used publicly available genetic data sets to interrogate the genetic correlation between JIA and 832 other health‐related traits using linkage disequilibrium score regression. Two‐sample Mendelian randomization (2SMR) was used to examine four genetic correlates for evidence of causality. Results: We found robust evidence (adjusted P [ P adj ] < 0.05) of genetic correlation between JIA and rheumatoid arthritis (genetic correlation [ r g ] = 0.63, P adj  = 0.029), hypothyroidism/myxedema ( r g  = 0.61, P adj  = 0.041), celiac disease (CD) ( r g  = 0.58, P adj  = 0.032), systemic lupus erythematosus ( r g  = 0.40, P adj  = 0.032), coronary artery disease (CAD) ( r g  = 0.42, P adj  = 0.006), number of noncancer illnesses ( r g  = 0.42, P adj  = 0.016), paternal health ( r g  = 0.57, P adj  = 0.032), and strenuous sports ( r g  = −0.52, P adj  = 0.032). 2SMR analyses found robust evidence that genetic liability to JIA was causally associated with the number of noncancer illnesses reported by UK Biobank (UKBB) participants (increase of 0.03 noncancer illnesses per doubling odds of JIA, 95% confidence interval 0.01‐0.05). Conclusion: This study illustrates genetic sharing between JIA and a diversity of health outcomes. The causal association between genetic liability to JIA and noncancer illnesses suggests a need for broader health assessments of patients with JIA to reduce their potential comorbid burden. The strength of genetic correlation with hypothyroidism and CD implies that patients with JIA may benefit from CD and thyroid function screening. Strong positive genetic correlation between JIA and CAD supports the need for cardiovascular risk assessment and risk factor modification.